Advanced sensing of volatile organic compounds in the fermentation of kombucha tea extract enabled by nano-colorimetric sensor array based on density functional theory. (30th March 2023) - Kang, Wencui; Lin, Hao; Yao-Say Solomon Adade, Selorm; Wang, Zhen; Ouyang, Qin; Chen, Quansheng
Highlights: Nano-modified materials MOF, PSA and PSN were employed in nano-CSA fabrication. The response mechanisms of CRMs exposure to VAs by DFT were analyzed. Nano-CSA to detect the dynamic changes of aroma components was investigated. Abstract: Volatile organic compounds (VOCs) released by food serve as monitoring indicators during fermentation. Thus the demand for highly sensitive and selective biosensors to VOCs is increasing. The current work proposed a novel nano-colorimetric sensor array (nano-CSA) composed of nano-chemo-responsive materials (CRMs) to quantify volatile alcohols (VAs) in the kombucha tea extract fermentation process. The density-functional theory results suggest that CRMs sensitive to VAs have small energy level differences. The higher the energy of the substance itself, the greater the density of the electron cloud and the stronger the reactivity. The higher the binding energy value, the more stable the molecule structure. The larger the angle and the shorter the centroid distance between CRMs and VAs, promote their effective integration. The work confirmed that the CRM-based nano-CSA is crucial in differentiating VAs employed to evaluate the kombucha tea extract fermentation degree with a 98.99% of variance contribution rate by principal component analysis.